EFFECT OF HEAT TREATMENT ON ELECTRICAL AND MECHANICAL PROPERTIES OF THE SOLID SAPROPEL (ENVIRONMENT. TECHNOLOGY. RESOURCES. Proceedings of the International Scientific and Practical Conference, 2017)
In this work changes of electrical and mechanical properties (hardness) of the solid sapropel after its heat treatment were researched. Changes of real and imaginary parts of dielectric permittivity, dielectric losses and specific electrical resistance depending on electrical field frequency in the range 0.01Hz- 1MHz were observed. Temperature dependences of AC (at 1 kHz) and DC electrical conductivity were studied. Chemical sample composition, IR spectra and structure of the solid sapropel were investigated. Heat treatment has a noticeable effect on the electrical characteristics of solid sapropel due to the strong influence of water on the charge transfer in this complex material. Charge transfer occurs predominantly due to ion migration and demonstrates strong dependence upon hydration - dehydration processes. After the heat treatment of the solid sapropel at the temperature of 1000C its hardness doesn’t change. If the sample of the solid sapropel is subjected to 20 min heat treatment at the temperature of 1500C, its hardness decreases by 5.4%, the number of C=C bonds decreases by 6.3±0.1%, the number of C=N bonds decreases by 2.2±0.1%, the number of C-C bonds decreases by 1,7±0.1%, the number of C-H bonds increases by 18.5±0.3%. It shows that in the temperature range 100-1500C destructive processes of the solid sapropel start, although visually (with optical microscope and with SEM) changes of structure are impossible to observe yet.